NG2-mediated Rho activation promotes amoeboid invasiveness of cancer cells - Paňková, Daniela; Jobe, Njainday; Kratochvílová, Magdalena; Buccione, Roberto; Brábek, Jan; Rösel, Daniel (European journal of cell biology, 2012)
The aim of this study was to analyze the potential role of NG2 chondroitin sulfate proteoglycan in amoeboid morphology and invasiveness of cancer cells. In the highly metastatic amoeboid cell lines A3 and A375M2, siRNA-mediated down-regulation of NG2 induced an amoeboid-mesenchymal transition associated with decreased invasiveness in 3D collagen and inactivation of the GTPase Rho. Conversely, the expression of NG2 in mesenchymal sarcoma K2 cells as well as in A375M2 cells resulted in an enhanced amoeboid phenotype associated with increased invasiveness and elevated Rho-GTP levels. Remarkably, the amoeboid-mesenchymal transition in A375M2 cells triggered by NG2 down-regulation was associated with increased extracellular matrix-degrading ability, although this was not sufficient to compensate for the decreased invasive capability caused by down-regulated Rho/ROCK signaling. Conversely, in K2 cells with overexpression of NG2, the ability to degrade the extracellular matrix was greatly reduced. Taken together, we suggest that NG2-mediated activation of Rho leading to effective amoeboid invasiveness is a possible mechanism through which NG2 could contribute to tumor cell invasion and metastasis.
Keywords: down regulace; Neoplasms; Up-Regulation; Cell Line, Tumor; membránové proteiny; Membrane Proteins; Neoplasm Invasiveness; upregulace; rho GTP-Binding Proteins; kolagen; Rho proteiny vázající GTP; extracelulární matrix; molekulární konformace; Cell Movement; Chondroitin Sulfate Proteoglycans; RNA, Small Interfering; krysa rodu Rattus; kinázy asociované s Rho; Animals; Down-Regulation; lidé; Humans; malá interferující RNA; zvířata; invazivní růst nádoru; Collagen; Extracellular Matrix; pohyb buněk; Rats; chondroitinsulfát proteoglykany; rho-Associated Kinases; nádory; Molecular Conformation; nádorové buněčné linie